1966
DOI: 10.1111/j.1365-2621.1966.tb01889.x
|View full text |Cite
|
Sign up to set email alerts
|

Certain Physiological and Biochemical Changes in Greenhouse‐Grown Tomatoes (Lycopersicon Esculentum Mill.)

Abstract: SUMMARY Tomatoes of V. R. Moscow and Fireball varieties grown in a greenhouse varied markedly from previously reported data on field‐grown lots of the same varieties with regards to total titratable acidity, color development, free reducing sugars, pectins, volatile reducing substances (VRS), organic acids, and ascorbic acid. Concentrations of all the nonvolatile attributes except total titratable acidity (%) were low as compared with field‐ripened tomatoes. Lower concentrations of VRS, organic acids (mg/100 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1971
1971
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Thus, citrate is present in quantities potentially able to displace all pectin‐bound Ca 2+ . Citrate and malate concentrations increase during ripening (Dalal et al ., 1966; Islam et al ., 1996), compatible with a role in softening. Such a role is supported by the observation that pectin solubilization in disks of unripe tomato pericarp is inhibited by added Ca 2+ (Mingani et al ., 1995).…”
mentioning
confidence: 99%
“…Thus, citrate is present in quantities potentially able to displace all pectin‐bound Ca 2+ . Citrate and malate concentrations increase during ripening (Dalal et al ., 1966; Islam et al ., 1996), compatible with a role in softening. Such a role is supported by the observation that pectin solubilization in disks of unripe tomato pericarp is inhibited by added Ca 2+ (Mingani et al ., 1995).…”
mentioning
confidence: 99%
“…Much of the aroma appears to be associated with the calyx; however, it is unfortunately lost before the fruit reaches the consumer via the markets. Dalal et al (1965Dalal et al ( , 1966 found that the total volatile reducing substances increased continuously as tomatoes matured and ripened.…”
Section: 59volatile Componentsmentioning
confidence: 99%
“…It is therefore well recognized that plants grown in a glasshouse differ from plants grown in the field (i.e. see Dalal et al ., ). It is also known that genotypic expression is often dependent on the environment, and genetic parameters estimated in glasshouse experiments may differ from those expressed in the field (Falconer and Mackay, ; Gillespie and Turelli, ).…”
Section: Introductionmentioning
confidence: 97%